Microbiota and particulate matter assessment in Portuguese optical shops providing contact lens services - Viegas, Carla (2017)
The aim of this work was to assess the microbiota (fungi and bacteria) and particulate matter in optical shops, contributing to a specific protocol to ensure a proper assessment. Air samples were collected through an impaction method. Surface and equipment swab samples were also collected side-by-side. Measurements of particulate matter were performed using portable direct-reading equipment. A walkthrough survey and checklist was also applied in each shop. Regarding air sampling, eight of the 13 shops analysed were above the legal requirement and 10 from the 26 surfaces samples were overloaded. In three out of the 13 shops fungal contamination in the analysed equipment was not detected. The bacteria air load was above the threshold in one of the 13 analysed shops. However, bacterial counts were detected in all sampled equipment. Fungi and bacteria air load suggested to be influencing all of the other surface and equipment samples. These results reinforce the need to improve air quality, not only to comply with the legal requirements, but also to ensure proper hygienic conditions. Public health intervention is needed to assure the quality and safety of the rooms and equipment in optical shops that perform health interventions in patients